Grey Relational Analysis (GRA) for optimization of CO2 laser cutting of stainless steel. (2023) - Senthilkumar, V.; Adinarayanan, A.; Jagatheesan, K.
Abstract: Laser cutting is a non-traditional industrial technique for cutting a variety of materials. The major goal of this study is to examine the influence of variables such as stand off distance, laser beam power, gas pressure and speed of cut on the width of the kerf, hardness, and roughness for CO2 laser cut of stainless steel. For the experimental plan, Taguchi's L9 orthogonal array was used. In the experiment, 4 cutting parameters were used: laser beam power (3400, 3700 and 4000 W), speed of cut (2200, 3100 and 4000 mm/min), gas pressure (0.7, 1and 1.3 bar) and stand off distance (0.6, 0.9, 1.2 mm). Laser cutting of AISI 304 stainless steel with a variety of performance characteristics is addressed using a grey grade derived from grey relational analysis. The grey grade reveal that speed of cut has a greater impact on the responses like hardness, width of the kerf and MRR than laser beam power, gas pressure and standoff distance. With this GRA technique, it is evident that the mentioned laser cutting performance characteristics can be optimized.